Reliability and validity of the revised impact on family scale (RIOFS) in the hospital context - Yorschua F. Jalil; Gregory S. Villarroel; Alejandra A. Silva; Lilian S. Briceño; Vanessa Perez Ormeño; Nicolas S. Ibáñez; Paulina A. Méndez; Cristina F. Canales; Mireya A. Méndez (SpringerOpen, 2019)
Abstract Background The lack of formal instruments to measure Burden in primary caregivers of Children in a hospital context is limited because mostly of published instruments are related to cancer survivors, ambulatory environment or general context for children with chronic conditions, but none of them adapted property to prolonged hospitalization context. This leaves the rising population of hospitalized chronic children's caregivers without a proper assessment. The aim of this study was to develop a version of the Revised Impact on Family Scale adapted to primary caregivers of chronic hospitalized children. A cross-sectional study with two main stages was conducted. The first one describes the linguistic and contextual adaptation process of the instrument, and the second refers to the psychometric testing and analysis.. Results Less than 15% of the participants expressed problems with some adapted items in the scale. Eighty-six caregivers were evaluated at Josefina Martinez Hospital, mostly female (34.2 ± 11.6 years old). Majority of participants were graduated from high school, salaried employee and mothers of the chronic child. The scale exhibits a high level of internal consistency (Cronbach's alpha 0.73), excellent intra-observer reliability (Intraclass Correlation Coefficient 0.9), acceptable empirical evaluation of content validity and low and negative construct validity (Pearson's correlation coefficient − 0.23). Conclusions This adapted version of the Revised Impact on Family Scale to the hospital context is a reliable, valid, self-administered and simple instrument to implement in order to assess the burden of primary caregivers with chronic hospitalized children.